2006
DOI: 10.1182/blood-2006-02-001495
|View full text |Cite
|
Sign up to set email alerts
|

Survival advantage from imatinib compared with the combination interferon-α plus cytarabine in chronic-phase chronic myelogenous leukemia: historical comparison between two phase 3 trials

Abstract: In the multinational IRIS study comparing imatinib with interferon plus cytarabine (IFN/Ara-C) in patients with newly diagnosed chronic-phase chronic myelogenous leukemia (CP CML), imatinib demonstrated significantly higher rates of complete cytogenetic responses (CCyRs) and improved progression-free survival (PFS). However, because of a high early crossover rate to imatinib, survival benefit was not assessable. Here, we report the result of a study comparing long-term outcome of patients included in 2 prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(141 citation statements)
references
References 25 publications
8
129
0
3
Order By: Relevance
“…The recent follow-up from the International Randomized Study of Interferon and ST1571 reported an estimated OS at 5 years of 89% for the imatinib cohort. 3 On the basis of these impressive results and those of others, 4,5 which further confirmed the superiority of imatinib to other therapies (for example, a-IFN, cytarabine), long-term tyrosine kinase inhibitor therapy has since become the gold standard for treatment of CML in first chronic phase (CP1).…”
Section: Introductionmentioning
confidence: 61%
“…The recent follow-up from the International Randomized Study of Interferon and ST1571 reported an estimated OS at 5 years of 89% for the imatinib cohort. 3 On the basis of these impressive results and those of others, 4,5 which further confirmed the superiority of imatinib to other therapies (for example, a-IFN, cytarabine), long-term tyrosine kinase inhibitor therapy has since become the gold standard for treatment of CML in first chronic phase (CP1).…”
Section: Introductionmentioning
confidence: 61%
“…26,27 The survival benefits of imatinib could not be determined in the IRIS study because of the high rate of patient crossover, but they were confirmed by historic comparison studies. 28,29 A retrospective comparison of newly diagnosed patients with CML who received imatinib (n ¼ 279) or IFN (n ¼ 650) at The University of Texas M. D. Anderson Cancer Center (MDACC) demonstrated improved response and survival for imatinib-treated patients. 28 CCyR rates were 87% for imatinib-treated patients versus 28% for IFNtreated patients (P < .001).…”
Section: Imatinib Nilotinib Dasatinibmentioning
confidence: 99%
“…Another retrospective study that examined outcomes from the imatinib arm of the IRIS trial and the IFN/cytarabine arm of the CML91 trial was in complete concordance with the MDACC study. 29 The safety, response, and survival advantages of imatinib over IFN has led to broad acceptance of imatinib as the drug of choice for initial therapy of CML. [21][22][23] Assessing imatinib response and resistance…”
Section: Imatinib Nilotinib Dasatinibmentioning
confidence: 99%
“…Imatinib mesylate (Gleevec, Novartis Basel, Switzerland; STI571), a Kit, Abl and PDGFR inhibitor, induces apoptosis of the Ph 1 CML progenitors by suppressing the ability of BCR/ABL to phosphorylate substrates through competitive inhibition at the BCR/ABL ATP binding site (Druker et al, 1996). The development of the BCR/ABL tyrosine kinase inhibitor imatinib mesylate (Gleevec; formerly STI571) as the treatment of choice for chronic phase CML and its remarkable therapeutic effects suggest that blast crisis transition will be postponed for several years in the majority of CML patients (Deininger et al, 2005a;Roy et al, 2006). However, the persistence of BCR/ABL transcripts in a cohort of patients with complete cytogenetic response (Hughes et al, 2003) and the resistance of the primitive CML stem cell to imatinib treatment (Copland et al, 2006) raises the possibility that treatment with imatinib alone might delay but not prevent disease progression.…”
Section: CML Bcr/abl and Imatinibmentioning
confidence: 99%